2007
DOI: 10.1074/jbc.m701327200
|View full text |Cite
|
Sign up to set email alerts
|

Residues Surrounding Arg336 and Arg562 Contribute to the Disparate Rates of Proteolysis of Factor VIIIa Catalyzed by Activated Protein C

Abstract: Activated Protein C (APC) inactivates factor VIIIa by cleavage at Arg 336 and Arg 562 within the A1 and A2 subunits, respectively, with reaction at the former site occurring at a rate ϳ25-fold faster than the latter. Recombinant factor VIII variants possessing mutations within the P4-P3 sequences were used to determine the contributions of these residues to the disparate cleavage rates at the two P1 sites. variant showed a modest increase in cleavage rate (ϳ4-fold) at Arg 562 compared with WT, whereas these r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 31 publications
2
33
1
Order By: Relevance
“…In an earlier study examining APC-catalyzed cleavage and inactivation of factor VIIIa, which like factor Xa, attacks Arg 336 initially and Arg 562 second- (15). This rate reduction was attributed to replacement of critical flanking residues with residues less optimal for cleavage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In an earlier study examining APC-catalyzed cleavage and inactivation of factor VIIIa, which like factor Xa, attacks Arg 336 initially and Arg 562 second- (15). This rate reduction was attributed to replacement of critical flanking residues with residues less optimal for cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of factor VIIIa inactivation, and A1 cleavage were calculated by dividing the absolute value of B by factor Xa concentration and results are expressed in nanomolar FVIIIa/min/nM factor Xa or nanomolar A1/min/nM factor Xa (15).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cleavage at the former site, which correlates with loss of function, appears to alter the orientation of A2 subunit with the A1/ A3C1C2 dimer (15), while cleavage at the latter site destroys a FXa-interactive site (16). These cleavages that inactivate FVIIIa occur at a slower rate than the activating cleavages catalyzed by FXa (12,17,18) and this property favors FXa as initially serving to activate FVIII. We have previously shown that P4-P3' residues flanking the Arg336 and Arg562 sites contribute towards determining rates of activated protein C (APC) or FXa cleavage at these sites (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%